ESTABLISHING THE RELATIONSHIP BETWEEN TEACHERS’ SELF – EFFICACY AND FORMATIVE ASSESSMENT: A LITERATURE REVIEW - Panagiotidou, Athanasia (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The contribution of formative assessment in teaching and learning process has been widely proven to be very important. The role of teachers in its implementation is also really crucial. However, the way in that formative assessment is implemented in the educational context is not satisfactory for many reasons. Although personal and contextual factors are really important in order for teachers to apply formative assessment practices, it seems that studies and systematic analysis about this topic are rare. This literature review aims to shed light on the relationship between self-efficacy as an important personal factor in implementing formative assessment and formative assessment itself. The results of this literature review showed that more studies need to be carried out in order to gain a better understanding.